Criminal Responsibility for Self-Use of Narcotics (Study of Case Decision Number: 309/PID.SUS/2017/PT.DKI) - Mutia Rahayu; Nining Yurista Prawitasari (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study discusses the application of criminal law in drug abuse cases analyzed through a study of the decision of case number: 309/PID.SUS/2017/PT.DKI. The main focus of the study is how the indictment, demands, and legal considerations by the judge reflect the values ​​of substantive and procedural justice, as well as how criminal law and the theory of justice are implemented in judicial practice. In this case, the defendant was charged with violating Article 112 paragraph (1) and Article 127 paragraph (1) letter a of Law No. 35 of 2009 concerning Narcotics. The judge sentenced him to imprisonment accompanied by medical and social rehabilitation, reflecting proportional efforts in imposing sanctions. This study also highlights how inequality in legal treatment of drug users still occurs, as well as the importance of reforming drug law policies to be more oriented towards restorative justice. The study emphasizes that true justice in drug cases must emphasize imprisonment to provide a deterrent effect rather than paying attention to the rehabilitation dimension.